THE VOCABULARY MASTERY OF THE SEVENTH GRADE STUDENTS OF SMP NEGERI 4 BAUBAU BY USING ANIMATION VIDEO - Lisa Julianti; Sanaria Maneba; Nur Melansari (English Education Journal, 2022)
The problem statement of this research was does the use of animation video improve the vocabulary mastery of seventh grade students of SMP Negeri 4 Baubau. The objective of this research was to find out whether or not the use of animation video improve the vocabulary mastery of seventh grade students of SMP Negeri 4 Baubau. The type of the research was a quantitative research with applying quasi- experimental method. The population was the seventh grade students of SMP Negeri 4 Baubau as many as 325 students. The sample was taken using cluster random sampling amounted 58 students. The data collection was carried out by using an instrument that was test. The data obtained were analyzed by descriptive statistics and inferential statistics. Based on the results of data analysis, it can be concluded that there is a significant effect of the application of animation video on the vocabulary mastery of seventh grade students at SMP Negeri 4 Baubau. The t-test results show that the probability value (t-count) is 2.295 and sig (2-tailed) is 0.025 which is less than 0.05 so that the alternative hypothesis (Ha) is accepted and the null hypothesis (HO) is rejected. It means, there is a significant effect before and after the application of animation video, as well as the average value of pre-test and post-test experimental class 51.55 to 80.76. as well as the control class 55.24 to 70.28.